Thymoquinone protection against 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin induced nephrotoxicity in rats. (16th November 2020) - Erdemli, Mehmet Erman; Yigitcan, Birgul; Erdemli, Zeynep; Gul, Mehmet; Bag, Harika Gozukara; Gul, Semir
ABSTRACT: We investigated the effects of thymoquinone (TQ) on kidney tissues of Wistar rats with 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin (TCDD) induced nephrotoxicity. We used 50 rats divided into five groups; control, corn oil, TCDD, TQ, TCDD + TQ. We found that malondialdehyde (MDA), total oxidant status (TOS), blood urea nitrogen (BUN), creatinine, interleukin 6 (IL-6), tumor necrosis factor-α (TNF-α) levels in the TCDD treated group increased significantly compared to the other groups, while reduced glutathione (GSH), superoxide dismutase (SOD), catalase (CAT) and total antioxidant status (TAS) levels decreased in the TCDD group. In the TQ treated group, we found that GSH, SOD, CAT, TAS levels increased and MDA, TOS, IL-6 and TNF-α levels decreased compared to the other groups. The effects of TCDD on oxidative stress parameters, inflammatory markers and histological changes were ameliorated by TQ treatment.